Bioactive compounds extracted from patchouli via microwave-assisted hydrodistillation: A 36-year bibliometric and systematic review analysis - Ahmed A.M. Elnour; Nour Hamid Abdurahmani; Khalid Hamid Musa; Firdos M. Abdulla (Elsevier, 2024)
Background: Over the past 36 years, the extraction of bioactive compounds from patchouli (Pogostemon cablin) using Microwave-Assisted Hydrodistillation has garnered increasing interest, particularly in China. This research explored various applications, including pharmaceuticals, anti-inflammatory agents, cosmetics, and skincare technologies. This study aimed to identify knowledge gaps, guide research efforts, foster collaboration, and enhance our understanding of the acquisition of bioactive compounds from patchouli. Additionally, this study sought to address the scarcity of studies investigating the correlation between bioactive compounds extracted through Microwave-Assisted Hydrodistillation and their biological activities. Study Design: This study analyzed literature on Microwave-Assisted Hydrodistillation for extracting bioactive compounds from patchouli. It explored the connections between authors, countries, and keywords and evaluated the field's output over time. This research also identified key authors, journals, and institutions, emphasizing the significance of the extraction of bioactive compounds from patchouli. Furthermore, it offered recommendations for future research directions Methods: This study used bibliometric analysis to identify past and present research topics quantitatively and objectively, with a comprehensive literature overview. The analysis involved statistical analysis of relevant scientific literature indices, a data matrix, and visualization of co-citation, coupling, cooperative analysis, and co-word analyses. The VOS viewer and R-biblioshiny were used as co-occurrence analysis software, particularly for keywords. The study also involved a systematic search strategy to identify relevant literature. Results: The bibliometric maps of the study comprised of 2,904 documents extracted from EBSCO, DIMENSION, SCOPUS, and PUBMED. These maps encompassed co-authorship analyses of authors and countries, co-occurrence analyses of author keywords, and thematic evolution. The dataset contains information from 1987 to 2023 and includes 51 documents from 44 journals and books. The annual growth rate of the documents was 0 % and the average age was 914 years. Each record had an average of 2039 citations and 363 references. These documents were associated with 141 keywords and 802 author keywords. A total of 243 authors contributed to these documents, with only 3 documents authored by a single individual. On an average, each document had 549 co-authors, and approximately 3.922 % of the co-authors had international affiliations. Conclusion: The study concludes that there are significant opportunities for researchers from various countries to collaborate on research into "patchouli secondary metabolites and their biological applications." However, this study acknowledges the limitations of its specific set of keywords and suggests that alternative keywords can provide various insights. This study also highlights the need for further research in specific areas, particularly the Gulf Cooperation Council (GCC), Africa, the USA, and Asia, which have shown fewer links and connections in the patchouli research field.